SISTEM INFORMASI BERBASIS WEB SMA AL- MUKHTARIYAH MAMBEN LAUK BERBASIS PHP DAN MYSQL DENGAN FRAMEWORK CODEIGNITER - Suhartini, suhartini; Sadali, Muhamad; Putra, Yupi Kuspandi (Fakultas Teknik Universitas Hamzanwadi, 2020)
These days, the development of science and technology is increasingly rapid, especially information technology and telecommunications that provide an important role in human life, especially in the world of education. One of them is a website technology that has been widely used to help facilitate the delivery of information in schools. And one of the high schools in the village of Mamben Lauk, Wanasaba Subdistrict, which is called Al-Mukhtariyah High School, did not have a website. Based on this occasion the present researcher took the initiative to create a website for the school. This is the time for all schools in this day to have a website and use it as facility to deliver of information to students or the wider community. To build a website the researcher used the PHP programming language and MySQL database with the Code Igniter framework.DOI : 10.29408/jit.v3i1.1793